Fluorescence in situ hybridisation (FISH) analysis of Chromosome 1 and gene expression levels of MAD2 and BUB1 levels in premalignant stages of gastric tissue. - Amudha Somasekar (2011)
Gastric cancer is a common cause of cancer death in the world. The mortality rate from gastric cancer is high in UK as it often presents late, often with local or distant metastasis. This makes the treatment options limited. The pathogenesis of gastric cancer occurs in a multi step pathway with pre cancerous conditions leading to cancer eventually. It is important to understand this carcinogenic process (aneuploidy and abnormal gene expression levels) and the driving forces (eg. Helicobacter Pylori infection) which will enable us to alter the disease outcome.This series of experiment included cytogenetic investigation which involved obtaining gastric cells using brush cytology and using Fluorescent insitu hybridisation technique to look for aneuploidy levels of chromosome 1 and 4. These two chromosomes were chosen as chromosome 1 has been recently shown to be abnormal in early in premalignant stages of gastric cancer. Chromosome 4 was chosen as hyperploidy of chromosome 4 was the predominant chromosomal aberration in Barrett’s oesophagus. This study has shown that the aneuploidy level of chromosome 1 progressively increased with the progression of the histological stages according to the Correa’s premalignant gastric cancer pathway. Significant increase in aneuploidy levels of chromosome 1 was seen in H. Pylori associated gastritis, implying that H. Pylori play a very important role in the progression of the disease.Aneuploidy can occur due to various genetic defects that may potentially occur during mitosis. Spindle cell check points play a vital role in preventing the cells from proceeding to the anaphase stage if there is any defect in the kinetochore attachment. Certain genes like MAD2 and BUB1 are thought to be instrumental in controlling the spindle cell check points and it is believed a steady state of genes like MAD2 and BUB1 are required for this. In the second part of this study, the MAD2 and BUB1 expression levels were measured and correlated to the aneuploidy stages. There was no significant difference in their expression levels in patients with significant aneuploidy level. MAD2 levels were increased in H.Pyloriassociated gastritis, which implies that H. Pylori plays an important role in the pathogenesis of gastric cancer.